1990
DOI: 10.1185/03007999009111495
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-release indomethacin and sustained-release diclofenac sodium in the treatment of rheumatoid arthritis: A comparative controlled clinical trial

Abstract: The efficacy and tolerability of a new, controlled-release indomethacin (75 mg) tablet was compared to that of a sustained-release diclofenac sodium (100 mg) tablet in 84 patients with rheumatoid arthritis. The study was designed as a double-blind, double-dummy crossover trial, patients being allocated at random to receive 1 active tablet and 1 placebo tablet of the alternative medication at night for 4 weeks before being crossed over to the alternative treatment for a further 4 weeks. Patient and clinical ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Diclofenac (DCF) is a non-steroidal anti-inflammatory drug (NSAID) with strong antirheumatic, anti-inflammatory, analgesic and anti-pyretic properties [22], which is widely used in the treatment of rheumatoid arthritis, osteoarthritis, non-articular rheumatism and sport injuries [23][24][25]. It is used to relieve the symptoms of many diseases such as ankylosing spondylitis and acute muscle pain conditions [26].…”
Section: Page 4 Of 40mentioning
confidence: 99%
“…Diclofenac (DCF) is a non-steroidal anti-inflammatory drug (NSAID) with strong antirheumatic, anti-inflammatory, analgesic and anti-pyretic properties [22], which is widely used in the treatment of rheumatoid arthritis, osteoarthritis, non-articular rheumatism and sport injuries [23][24][25]. It is used to relieve the symptoms of many diseases such as ankylosing spondylitis and acute muscle pain conditions [26].…”
Section: Page 4 Of 40mentioning
confidence: 99%
“…To give a particular example, sodium Diclofenac is currently prescribed in 100 mg oral doses for chronic conditions, such as Rheumatoid Arthritis. 55,56 However, in extreme cases, larger doses can be prescribed, but only if the therapeutic benet outweighs the known adverse effects. The same amount of Diclofenac released from MgDiclo6 offers a slower release rate and only contains a small fraction of ∼3 mg of the daily recommended dose of Mg 2+ (∼300-400 mg).…”
Section: Cytotoxicity Of Tcps and Discussionmentioning
confidence: 99%
“…Slow release formulations like indomethacin micro granules, Sustain release capsules prepared by the centrifugation (Crowley et al, 2001). Clinical studies indicated comparable safety and efficacy profiles.…”
Section: Sustain Release Capsulesmentioning
confidence: 98%